PENGARUH BRAND EQUITY DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN LAYANAN INDIBIZ SEGMEN B2B PADA TELKOM UBUNG - Nadya Arinda Putri; I Wayan Wirga; I Made Widiantara (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to determine the influence of brand equity and price on the decision to purchase Indibiz services in the B2B segment at Telkom Ubung Region. This study uses a quantitative approach with data collection through the distribution of questionnaires to 62 Telkom B2B customers, using non-probability sampling techniques. Data analysis was conducted using multiple linear regression to test the relationship between brand equity (X1), price (X2), and purchase decisions (Y). The results of the study partially indicate that brand equity and price have a positive and significant effect on purchasing decisions. Simultaneously, both variables were also found to influence purchasing decisions for Indibiz services. The coefficient of determination value shows that brand equity and price can explain 76.8% of the variation in purchasing decisions. These findings have practical implications for Telkom Ubung Regional Management in designing more targeted marketing strategies to increase sales and customer satisfaction in the B2B market. By understanding the role of brand perception and price in influencing customer behavior, Telkom can align its service offerings with consumer needs and strengthen the company's competitive position in the market.